Protocol for a prospective observational study to improve prehospital notification of injured patients presenting to trauma centres in India. Issue 7 (17th July 2017) - Mitra, Biswadev; Mathew, Joseph; Gupta, Amit; Cameron, Peter; O'Reilly, Gerard; Soni, Kapil Dev; Kaushik, Gaurav; Howard, Teresa; Fahey, Madonna; Stephenson, Michael; Kumar, Vineet; Vyas, Sharad; et al.
Abstract : Introduction: Prehospital notification of injured patients enables prompt and timely care in hospital through adequate preparation of trauma teams, space, equipment and consumables necessary for resuscitation, and may improve outcomes. In India, anecdotal reports suggest that prehospital notification, in those few places where it occurs, is unstructured and not linked to a well-defined hospital response. The aim of this manuscript is to describe, in detail, a study protocol for the evaluation of a formalised approach to prehospital notification. Methods and analysis: This is a longitudinal prospective cohort study of injured patients being transported by ambulance to major trauma centres in India. In the preintervention phase, prospective data on patients will be collected on prehospital assessment, notification, inhospital assessment, management and outcomes and recorded in a new tailored multihospital trauma registry. All injured patients arriving by ambulance and allocated to a red or yellow priority category will be eligible for inclusion. The intervention will be a prehospital notification application to be used by ambulance clinicians to notify emergency departments of the impending arrival of a patient. The proportion of eligible patients arriving to hospital after notification will be the primary outcome measure. Secondary outcomes evaluated will be availability of a trauma cubicle, presence of a trauma team on patient arrival, time to first chest X-ray and inhospital mortality. Progress: Ethical approval has been obtained from the All India Institute of Medical Sciences, New Delhi and site-specific approval granted by relevant trauma services. The trial has also been registered with the Monash University Human Research and Ethics Committee; Project number: CF16/1814 – 2016000929. Results will be fed back to prehospital and hospital clinicians via a series of reports and presentations. These will be used to facilitate discussions about service redesign and implementation. It is expected that evidence for improved outcomes will enable widespread adoption of this intervention among centres in all settings with less established tools for prehospital assessment and notification. Trial registration number: NCT02877342; Pre-results.